Advertising Budgeting: A Reinvestigation of the Evidence on Brand Size and Spend. Issue 1 (2nd January 2016) - Danenberg, Nick; Kennedy, Rachel; Beal, Virginia; Sharp, Byron
Abstract : Deciding on and justifying the size of advertising budgets is a common challenge that marketers face. We reinvestigate previously noted relationships between advertising spend and brand size for 11 countries, in two categories, for multiple media. We also investigate the longitudinal market share impact over five years of extra share-of-voice deviations from equilibrium share-of-voice calculated from share-of-voice equal to share-of-market (SoV = SoM) and Jones's advertising intensiveness curve (AI) relationship. We critique the usefulness of these approaches for advertising budgeting.